DESCRIPTIVE STUDIES OF KIDNEY FAILURE IN BANGAH VILLAGE, GEDANGAN SUB-DISTRICT - Afifah, Yeni Nur (Prodi keperawatan sidoarjo, politeknik kesehatan kemenkes surabaya indonesia, 2024)
Abstract Kidney failure is the inability of the kidneys to function adequately for the body's needs (must be assisted by dialysis or transplantation. Generally, patients are not aware that they are suffering from terminal kidney failure because this disease progresses gradually and takes years as the patient's kidney function declines. There are two general terms for Kidney Failure, namely, Acute Kidney Failure and Chronic Kidney Failure. According to 2018 World Health Organization (WHO) data, around 71% of deaths in the world are caused by Non-Communicable Diseases (PTM).In 2020, it is estimated that the death rate this will increase to 73%.The results of basic health research (Riskesdas) 2013, stated that Chronic Kidney Failure (CKD) increased from 20% to 38% in 2018. The problem is that the authors are interested in conducting research entitled